Vitamin D in Health and Disease: A Literature Review - Hend Abass; Zahraa Omran (The Iraqi Journal of Medical Sciences)
“Vitamin D” the ‘‘sunshine’’ vitamin is a hot topic that attracted ample attention over the past decades, specially that a considerable proportion of the worldwide population are deficient in this essential nutrient. By encouraging the absorption and metabolism of calcium and phosphate, vitamin D is an essential prohormone for maintaining the health of bones and muscles. A sizeable amount of the body's vitamin D requirements are synthesized by the human body using ultraviolet B (UVB) radiation from sunshine in addition to dietary sources such fatty fish, eggs, fortified milk, and cod liver oil. Vitamin D is available in two different forms: D2 and D3 (cholecalciferol). Vitamin D2 is a synthetic version that is frequently found in fortified foods and is sourced from plants, but vitamin D3 is synthesized by the skin after exposure to sunlight and may be obtained from animal sources. The main function of vitamin D is thought to be the body's absorption of calcium from the gut, which is essential for skeletal health (bone mineralization, remodeling, and maintenance). But hypovitaminosis D, also known as a vitamin D deficiency, can have an impact on the bones, muscles, brain, heart, and immune system, among other components of the body. As a result, the shortage causes serious illnesses like cancer, diabetes, autoimmune diseases, infections, rickets (in children), osteopenia, osteoporosis, hypertension, fractures and falls in adults, and neurological abnormalities. A complete understanding of vitamin D sources, serum vitamin D levels, and deficient symptoms, connected to various clinical diseases, requirement and maintenance in the body, length of sun exposure, and effective treatment dose, is an effective strategy for deficiency prevention. The importance of Vitamin D, the causes of its shortage, and the sources accessible will therefore be highlighted in the current review. Keywords: Vitamin D, synthesis, levels and functions, sources, deficiency Citation: Abass HA, Omran ZS. Vitamin D in health and disease: A literature review. Iraqi JMS. 2023; 21(2): 245-253. doi: 10.22578/IJMS.21.2.12